Évaluer les savoirs de l'expérience - Isabelle Cherqui-Houot (Les éditions de la Maison des sciences de l'Homme, 2007)
The changes in French universities contradict the traditional configuration of a balance between research activities and teaching. They profoundly modify perceptions that university actors could until now have of their own tasks and their legitimacy to use their prerogatives for the development, teaching and accreditation of knowledge. After an exploration of the procedures for accreditation of prior experiential learning in five universities, this contribution will analyse the practices of coaching and the functioning of juries in these universities. It will show in particular how those concerned make arrangements with the legal texts. It will explain how these new juries come to a decision of accreditation.